Encrypted Arabic Documents Search Model using Fuzzy Keywords in Cloud Computing - Nidal Hassan Hussein; Ahmed Khalid; Khalid Khanfar (Society of Visual Informatics, 2017)
Cloud computing is a burgeoning and revolutionary technology that has changed how data are stored and computed in the cloud. This technology incorporates many elements into an innovative architecture. Among them are autonomic computing, grid computing, and utility computing. Moreover, the rapid storage of data in the clouds has an impact on the security level of organizations. The chief challenge of cloud computing is how to build a secured cloud storage.The reason for this difficulty is thatbefore data transfer, data are usually encrypted in order to achieve a high utilization. Another real challenging task of cloud computing is how to apply a search over encrypted data. As many techniques support only exact keywordmatches, we propose a model to search over encrypted data that are written in Arabic. If an exact keyword match fails, our model will approximate the file as a secondary result. Our model will also use a fuzzy keyword search to enhance system usability by obtaining matching result whenever users input exact matches or the closest possible matches based on keywords. To the best of our knowledge, our model is considered to be the first research work that applies fuzzy search over Arabic encrypted data.